PSEN2 Mutations May Mimic Frontotemporal Dementia: Two New Case Reports and a Review - Minguillón Pereiro, Anxo Manuel; Quintáns Castro, Beatriz; Ouro Villasante, Alberto; Aldrey Vázquez, José Manuel; Cortés Hernández, Julia; Aramburu-Núñez, Marta; Arias Gómez, Manuel; Jiménez Martín, Isabel; Sobrino, Tomás; Pías-Peleteiro, Juan Manuel (Biomedicines, 2024)
Background: Monogenic Alzheimer’s disease (AD) has severe health and socioeconomic repercussions. Its rarest cause is presenilin 2 (PSEN2) gene mutations. We present two new cases with presumed PSEN2-AD with unusual clinical and neuroimaging findings in order to provide more information on the pathophysiology and semiology of these patients. Methods: Women aged 69 and 62 years at clinical onset, marked by prominent behavioral and language dysfunction, progressing to severe dementia within three years were included. The complete study is depicted. In addition, a systematic review of the PSEN2-AD was performed. Results: Neuroimaging revealed pronounced frontal white matter hyperintensities (WMH) and frontotemporal atrophy/hypometabolism. The genetic study unveiled PSEN2 variants: c.772G>A (p.Ala258Thr) and c.1073-2_1073-1del. Both cerebrospinal fluid (CSF) and experimental blood biomarkers shouldered AD etiology. Conclusions: Prominent behavioral and language dysfunction suggesting frontotemporal dementia (FTD) may be underestimated in the literature as a clinical picture in PSEN2 mutations. Thus, it may be reasonable to include PSEN2 in genetic panels when suspecting FTDL. PSEN2 mutations may cause striking WMH, arguably related to myelin disruption induced by amyloid accumulation.